Polyether acrylate rapid curing repair material, preparation method and application thereof
Patent Information
- Application Number
- CN202610927751.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]在低温环境下,甲基丙烯酸甲酯的固化速度较慢,且常规催化剂体系无法有效地促进低温下的聚合反应,导致修补层的强度和粘结性能不足
[0016](1)本发明提供的聚醚型丙烯酸酯快速固化修补材料在极地低温环境下可以快速固化成型,以满足人们的使用需求。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road repair materials technology, specifically relating to a polyether-type acrylate rapid-curing repair material and its preparation method and application. Background Technology
[0002] Methyl methacrylate (MDMA), as an important monomer, has been widely used in the development of road repair materials. In the field of concrete repair, MDMA can be used as a modifier for cement-based composite materials or as a standalone repair material. It possesses excellent low-temperature curing properties, fast curing speed, high strength, and strong chemical corrosion resistance, making it particularly suitable for rapid repair in harsh environments. However, while existing MDMA-based repair materials exhibit good mechanical properties, their application in special environments, especially under extreme low-temperature conditions and rapid repair requirements, still faces certain limitations.
[0003] First, traditional cement-based repair materials cure too slowly at low temperatures and cannot reach sufficient strength in a short time, limiting their use in special projects. Second, while existing organic resin repair materials possess good adhesion and durability, they are prone to performance degradation and insufficient frost resistance due to incomplete curing at extremely low temperatures. Furthermore, the curing and mechanical properties of existing methyl methacrylate (MMA)-based repair materials are difficult to maintain stability under extreme temperature conditions, and their chemical corrosion resistance and durability still need improvement. Therefore, developing high-performance MMA-based repair materials under complex conditions such as low temperature, high humidity, and rapid curing to meet the rapid construction needs of special environments is a pressing technical challenge.
[0004] At low temperatures, methyl methacrylate (MMA) cures slowly, and conventional catalyst systems cannot effectively promote the polymerization reaction at low temperatures, resulting in insufficient strength and adhesion of the repair layer. Although MMA has good mechanical properties at room temperature, its strength gain is slow at low temperatures, especially under conditions of large temperature variations, and its freeze-thaw resistance is poor, easily leading to cracking or peeling of the repair layer. Current repair materials based on traditional cement or conventional resins require long construction and curing periods, and due to environmental limitations, they often cannot meet the rapid needs of special environments and emergency repairs. Addressing these issues and improving the performance of repair materials, especially in extreme low-temperature environments, remains a pressing technical challenge. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a polyether-type acrylate rapid-curing repair material, which is obtained by mixing polymethyl methacrylate with a monomer mixture, polymerizing the mixture, and then mixing it with quartz sand. It enables rapid road repair under low-temperature conditions, exhibits good frost resistance, and strong adhesion, meeting the needs of users in low-temperature environments.
[0006] The purpose of this invention is to provide a polyether-type acrylate fast-curing repair material, which is obtained by mixing polymethyl methacrylate with a monomer mixture, polymerizing it, and then mixing it with quartz sand.
[0007] The monomer mixture includes one or more of methyl methacrylate (MMA), trimethylolpropane trimethacrylate (TMPTMA), α-methacrylic acid (MAA), and hydroxyethyl methacrylate (HEMA).
[0008] Preferably, polyethylene glycol dimethacrylate is added to the monomer mixture.
[0009] The present invention also aims to provide a method for preparing the polyether-type acrylate fast-curing repair material, wherein the method involves mixing polymethyl methacrylate with a monomer mixture, polymerizing the mixture, and then mixing it with quartz sand.
[0010] The method specifically includes the following steps:
[0011] Step 1: Mix the monomers to obtain a monomer mixture, then add polymethyl methacrylate and mix evenly to obtain a viscous liquid mixture;
[0012] Step 2: Add the initiator to the mixed viscous liquid to obtain the reaction liquid;
[0013] Step 3: Add quartz sand to the reaction liquid and mix well to obtain polyether-type acrylate fast-curing repair material.
[0014] Another object of the present invention is to provide an application of the aforementioned polyether-based acrylate rapid-curing repair material for road repair, particularly for road repair in environments ranging from -20°C to 40°C.
[0015] The present invention has the following beneficial effects:
[0016] (1) The polyether-type acrylate fast-curing repair material provided by the present invention can be rapidly cured and molded in the polar low temperature environment to meet people's needs.
[0017] (2) Using benzoyl peroxide (BPO) and N,N-dimethyl-p-toluidine (DMPT) as dual initiators, a redox reaction occurs, which can generate free radicals even at extremely low temperatures, thereby reducing the decomposition activation energy of peroxides, increasing the decomposition rate of peroxides, and improving the rate of free radical polymerization of acrylic resin.
[0018] (3) In this invention, the polyether-type acrylate is distributed between the gaps in the sand grains, playing a role in bonding and supporting. After the resin adhesive in the gaps between the sand grains cures, it will coat the surface of the sand grains, forming a polymer film and building a stable connecting bridge. The modification between monomers can reduce the gaps in the contact surface between the resin matrix and the sand grains, thereby enhancing the mechanical properties. This may be because the carboxyl groups and other groups on the functionalized resin matrix form renewable and unstable intermolecular forces with the surface of the desert sand. Attached Figure Description
[0019] Figure 1 The thermogravimetric curves of commercially available polymethyl methacrylate (PMMA) (viscosity-average molecular weight of approximately 100,000), mortar material PMMA / SiO2 of Comparative Example 1, mortar material I (Poly(MMAcoMAA) / SiO2), mortar material II (Poly(MMAcoTMPTMA) / SiO2), and mortar material III are shown. Detailed Implementation
[0020] The present invention will now be described in detail through specific embodiments, and the features and advantages of the present invention will become clearer and more explicit with these descriptions.
[0021] This invention provides a polyether-type acrylate fast-curing repair material, which is obtained by mixing polymethyl methacrylate with a monomer mixture, polymerizing it, and then mixing it with quartz sand.
[0022] The monomer mixture includes one or more of methyl methacrylate (MMA), trimethylolpropane trimethacrylate (TMPTMA), α-methacrylic acid (MAA), and hydroxyethyl methacrylate (HEMA).
[0023] Preferably, polyethylene glycol dimethacrylate is added to the monomer mixture.
[0024] The present invention also provides a method for preparing the polyether-type acrylate rapid curing repair material, wherein the method involves mixing polymethyl methacrylate with a monomer mixture, polymerizing the mixture, and then mixing it with quartz sand.
[0025] The method specifically includes the following steps:
[0026] Step 1: Mix the monomers to obtain a monomer mixture, then add polymethyl methacrylate and mix evenly to obtain a viscous liquid mixture.
[0027] The monomer mixture includes methyl methacrylate (MMA), and preferably, also includes one or more of trimethylolpropane trimethacrylate (TMPTMA), α-methacrylic acid (MAA), and hydroxyethyl methacrylate (HEMA).
[0028] The monomer mixture is 70-120 parts by weight, preferably 80-110 parts, and more preferably 90-100 parts.
[0029] The methyl methacrylate is present in parts by weight of 65-95, preferably 70-90, and more preferably 75-85.
[0030] The weight parts of trimethylolpropane trimethacrylate are 3-15 parts, preferably 4-12 parts, and more preferably 5-10 parts.
[0031] The amount of α-methacrylic acid (MAA) is 4-15 parts by weight, preferably 6-12 parts, and more preferably 8-10 parts.
[0032] The amount of hydroxyethyl methacrylate (HEMA) is 2-10 parts by weight, preferably 3-8 parts, and more preferably 4-6 parts.
[0033] Preferably, polyethylene glycol dimethacrylate is added to the monomer mixture. The amount of polyethylene glycol dimethacrylate is 6-18 parts by weight, preferably 7-15 parts, and more preferably 8-12 parts.
[0034] The mixing temperature is 10-40℃, preferably 15-35℃, and more preferably 20-30℃. The mixing time is 10-25 minutes, preferably 15-20 minutes.
[0035] Add polymethyl methacrylate (PMMA) in an amount of 9-31 parts by weight, preferably 12-28 parts, more preferably 15-25 parts. The PMMA is mixed at a temperature of 35-50°C, preferably 40-45°C. The mixing time is 3-6 hours, preferably 4-5 hours, until the PMMA is completely dissolved and the system is a homogeneous, transparent, viscous liquid.
[0036] Step 2: Add the initiator to the mixed viscous liquid to obtain the reaction liquid.
[0037] The viscous liquid mixture obtained in step 1 is cooled to 20-30°C, and an initiator is added. The initiator is selected from one or more acyl peroxides, preferably benzoyl peroxide (BPO), and its weight is 1-6 parts, more preferably 2-5 parts, and more preferably 3-4 parts. Preferably, a polymerization accelerator is also added, selected from one or more aromatic tertiary amine accelerators, preferably N,N-dimethyl-p-toluidine (DMPT), and its weight is 5-10 parts, more preferably 6-9 parts, and more preferably 7-8 parts.
[0038] Step 3: Add quartz sand to the reaction liquid and mix well to obtain polyether-type acrylate fast-curing repair material.
[0039] The mass ratio of the quartz sand to the reaction liquid is 1:(4-15), preferably 1:(4-10), and more preferably 1:6.
[0040] This invention also provides the application of the aforementioned polyether-type acrylate rapid-curing repair material for road repair, particularly for road repair in environments ranging from -20°C to 40°C.
[0041] Example
[0042] Example 1
[0043] At room temperature, 80 parts of methyl methacrylate (MMA) and 10 parts of α-methacrylic acid (MAA) were mixed. 20 wt% of PMMA (polymethyl methacrylate, viscosity-average molecular weight approximately 100,000) (18 parts) was added to the resin monomer mixture. The mixture was stirred and dissolved at 45°C for 4 hours. Once fully dissolved, the modified methyl methacrylate gelling material was obtained. After cooling to room temperature, 4 wt% of benzoyl peroxide (BPO) (3.6 parts) and 8 wt% of N,N-dimethyl-p-toluidine (DMPT) (7.2 parts) were added to the gelling material. After stirring for 3 minutes, the binder was mixed with desert sand at a mass ratio of 1:6 to obtain mortar material I (Poly(MMAcoMAA) / SiO2).
[0044] Example 2
[0045] At room temperature, 80 parts of methyl methacrylate (MMA) and 10 parts of trimethylolpropane trimethacrylate (TMPTMA) were mixed. 20 wt% of PMMA (polymethyl methacrylate, viscosity-average molecular weight approximately 100,000) (18 parts) was added to the resin monomer mixture. The mixture was stirred and dissolved at 45°C for 4 hours. Once fully dissolved, the modified methyl methacrylate cementitious material was obtained. After cooling to room temperature, 4 wt% of benzoyl peroxide (BPO) (3.6 parts) and 8 wt% of N,N-dimethyl-p-toluidine (DMPT) (7.2 parts) were added to the cementitious material. After stirring for 3 minutes, the binder and desert sand were mixed evenly at a mass ratio of 1:6 to obtain mortar material II (Poly(MMAcoTMPTMA) / SiO2).
[0046] Example 3
[0047] 80 parts MMA, 10 parts PEGDMA (polyethylene glycol dimethacrylate, Mn=400), 5 parts hydroxyethyl methacrylate (HEMA), and 5 parts TMPTMA were added sequentially to a reaction vessel and mechanically stirred at 500 rpm for 15 minutes at room temperature to ensure thorough mixing of the monomers, resulting in a transparent and homogeneous mixture of polyether-type functionalized monomers.
[0048] Add 20 wt% PMMA powder (20 parts) to the above monomer mixture. Heat in a 45°C water bath and stir continuously at 600 rpm for 4 hours until the PMMA is completely dissolved and the system becomes a uniform, transparent, viscous liquid, thus obtaining the modified methyl methacrylate gelling material. Cool to room temperature (25°C), add 4 wt% BPO (4 parts) and 8 wt% DMPT (8 parts) to the monomer mixture. After stirring for 3 minutes, mix with desert sand at a mass ratio of 1:6 (binder:sand) to obtain mortar material III.
[0049] Comparative Example
[0050] Comparative Example 1
[0051] PMMA (polymethyl methacrylate, with a viscosity-average molecular weight of approximately 100,000) was mixed with desert sand at a mass ratio of 1:6 to obtain the mortar material PMMA / SiO2.
[0052] Experimental Example
[0053] Experimental Example 1
[0054] Thermogravimetric analysis (TGA) was performed on commercially available polymethyl methacrylate (PMMA) (viscosity-average molecular weight approximately 100,000), mortar material PMMA / SiO2 (Comparative Example 1), mortar material I (Poly(MMAcoMAA) / SiO2), mortar material II (Poly(MMAcoTMPTMA) / SiO2), and mortar material III. The test results are as follows: Figure 1 As shown.
[0055] The 5% thermal decomposition temperature (TWD) of commercially available PMMA in air is approximately 326.7℃. The PMMA / SiO2 sample of Comparative Example 1, a mortar material, has a TWD of approximately 229.5℃ in air, with a remaining mass of 85.5%. The mortar material I (Poly(MMAcoMAA)SiO2) sample has a TWD of approximately 303.5℃ in air, with a remaining mass of 84.67%. The binder-to-mortar ratio increased from 1:6 to 1:5.7. Furthermore, a slight weight loss was observed near 100℃, possibly due to unreacted monomers during curing. The decomposition temperature of the modified mortar repair material increased, presumably because the addition of MAA resulted in a greater exothermic polymerization reaction, promoting a rise in relative molecular mass. However, this increased exothermic reaction also caused monomers to volatilize and be lost during polymerization, which aligns with the increased binder-to-mortar ratio. The 5% thermal decomposition temperature of mortar material II (Poly(MMAcoTMPTMA) / SiO2) sample in air was approximately 327.28℃, with a remaining mass of 86.22%. The binder-mortar ratio was close to 1:6. The increased thermal decomposition temperature was due to the easier formation of high molecular weight copolymers after cross-linking, indicating that the introduction of TMPTMA not only facilitated the polymerization reaction but also improved the material's performance. Compared to commercially produced PMMA, the MMA copolymers formed by the cured MAA and TMPTMA modified repair materials, despite having a higher initiator content, still yielded products with higher molecular weights. Because the simulated mortar sample preparation process did not involve high-temperature curing, the thermal decomposition temperature was not increased compared to commercially produced PMMA, but the modifier could compensate for the negative impact of the polymerization conditions. Mortar material III exhibited a lower 5% thermal decomposition temperature and a higher remaining mass.
[0056] Experimental Example 2
[0057] The mortar material I prepared in Example 1 was quickly placed on a horizontally placed substrate, and the bond strength was tested. At an ambient temperature of 0°C, the bond strength was 3.7-3.8 MPa when the substrate humidity was 0.5% (RH); and 3.1-3.3 MPa when the substrate humidity was 5% (RH). At -20°C, the bond strength was 3.6 MPa when the substrate humidity was 0.5%; and 2.5-2.7 MPa when the substrate humidity was 5%.
[0058] Experimental Example 3
[0059] Standard specimens were prepared according to the test method of GB / T17671-1999, and compressive strength tests were conducted. The test temperatures were 0℃ and -20℃.
[0060] The mortar material I prepared in Example 1 has a compressive strength of 80.9 MPa after curing at 0℃ for 1 hour and 96.3 MPa after curing at -20℃ for 1 hour.
[0061] The mortar material II prepared in Example 2 has a compressive strength of 89.7 MPa after curing at 0℃ for 1 hour and 89.6 MPa after curing at -20℃ for 1 hour.
[0062] The mortar material III prepared in Example 3 has a compressive strength of 94.2 MPa after curing at 0℃ for 1 hour and 91.8 MPa after curing at -20℃ for 1 hour.
[0063] The present invention has been described in detail above with reference to specific embodiments and / or exemplary examples, as well as the accompanying drawings. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A polyether-type acrylate fast-curing repair material, which is obtained by mixing polymethyl methacrylate with a monomer mixture, polymerizing it, and then mixing it with quartz sand.
2. The polyether-type acrylate rapid-curing repair material according to claim 1, characterized in that, The monomer mixture includes one or more of methyl methacrylate, trimethylolpropane trimethacrylate, α-methacrylic acid, and hydroxyethyl methacrylate. Preferably, polyethylene glycol dimethacrylate is added to the monomer mixture.
3. A method for preparing the polyether-type acrylate rapid-curing repair material according to claim 1 or 2, characterized in that, The method involves mixing polymethyl methacrylate with a monomer mixture, polymerizing it, and then mixing it with quartz sand.
4. The method according to claim 3, characterized in that, The method specifically includes the following steps: Step 1: Mix the monomers to obtain a monomer mixture, then add polymethyl methacrylate and mix evenly to obtain a viscous liquid mixture; Step 2: Add the initiator to the mixed viscous liquid to obtain the reaction liquid; Step 3: Add quartz sand to the reaction liquid and mix well to obtain polyether-type acrylate fast-curing repair material.
5. The method according to claim 4, characterized in that, In step 1, the monomer mixture includes methyl methacrylate (MMA), and preferably, also includes one or more of trimethylolpropane trimethacrylate (TMPTMA), α-methacrylic acid (MAA), and hydroxyethyl methacrylate (HEMA). The monomer mixture is present in parts by weight of 70-120, preferably 80-110, and more preferably 90-100. Preferably, polyethylene glycol dimethacrylate is added to the monomer mixture. The amount of polyethylene glycol dimethacrylate is 6-18 parts by weight, preferably 7-15 parts, and more preferably 8-12 parts.
6. The method according to claim 5, characterized in that, In step 1, The methyl methacrylate is present in parts by weight of 65-95 parts. The weight of trimethylolpropane trimethacrylate is 3-15 parts. The α-methacrylic acid is present in parts by weight of 4-15 parts. The weight of hydroxyethyl methacrylate is 2-10 parts.
7. The method according to claim 6, characterized in that, In step 1, polymethyl methacrylate (PMMA) is added, with a weight of 9-31 parts.
8. The method according to claim 4, characterized in that, In step 2, the mixed viscous liquid obtained in step 1 is cooled to 20-30°C, and an initiator is added. The initiator is selected from one or more acyl peroxides, preferably benzoyl peroxide (BPO). Preferably, a polymerization accelerator is also added, selected from one or more aromatic tertiary amine accelerators, preferably N,N-dimethyl-p-toluidine.
9. The method according to claim 4, characterized in that, In step 3, the mass ratio of the quartz sand to the reaction liquid is 1:(4-15).
10. The application of the polyether-type acrylate rapid-curing repair material according to claim 1 or 2, characterized in that, Used for repairing damage.